Polarization Singularity Explosions in Tailored Light Fields (Laser Photonics Rev. 12(6)/2018). Issue 6 (14th June 2018) - Otte, Eileen; Alpmann, Christina; Denz, Cornelia
Abstract : Singular Optics Optical singularities belong to the most fundamental properties of light. In article number1700200, Eileen Otte and co‐workers tailor and investigate singularity "explosions" by combining perturbed higher‐order phase and polarization singularities. These complex spatio‐temporal propagation dynamics include singularity unfolding, type conversion, annihilation and creation, revealing fascinating properties of structured light fields.